2013
DOI: 10.1002/adfm.201303471
|View full text |Cite
|
Sign up to set email alerts
|

8.91% Power Conversion Efficiency for Polymer Tandem Solar Cells

Abstract: A power conversion effi ciency of up to 8.91% is obtained for a solution-processed polymer tandem solar cells based on a large-bandgap polymer, poly(4,4-dioctyldithieno(3,2-b:2′,3′-d)silole)-2,6-diyl-alt -(2,1,3benzothiadiazole)-4,7-diyl) with a polymeric interconnecting layer to electrically connect the front and rear subcells, demonstrating that proper device and interface engineering are can improve the performance of polymer tandem solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…PBDTTT polymers have been widely selected as the photoactive materials in double junction OPVs owing to the advantage of excellent EQE values (>70%) in the whole wavelength region. [80][81][82][83][84][85][86] Zhou et al [ 80 ] fi rst explored the PBDTTT-C/PCBM blend as red absorber and designed a double junction OPV with a polymer inter-connect layer. The best-performing device achieved a V oc of 1.50 V, a J sc of 7.7 mA cm −2 , and a large FF of 72%, yielding a PCE of 8.2%.…”
Section: Multiple Junction Opvs Based On Well-known Pbdttt Polymersmentioning
confidence: 99%
“…PBDTTT polymers have been widely selected as the photoactive materials in double junction OPVs owing to the advantage of excellent EQE values (>70%) in the whole wavelength region. [80][81][82][83][84][85][86] Zhou et al [ 80 ] fi rst explored the PBDTTT-C/PCBM blend as red absorber and designed a double junction OPV with a polymer inter-connect layer. The best-performing device achieved a V oc of 1.50 V, a J sc of 7.7 mA cm −2 , and a large FF of 72%, yielding a PCE of 8.2%.…”
Section: Multiple Junction Opvs Based On Well-known Pbdttt Polymersmentioning
confidence: 99%
“…Previously, we demonstrated the realization of all-solution-processed all-plastic singlejunction solar cells using layers of the conducting polymer poly (3,4- [34][35][36][37] Despite these advances, the realization of all-solution-processed all-plastic tandem solar cells is still challenging. This is because the PEDOT:PSS/PEI CRL used in those tandem cells required to be patterned (due to the high conductivity) in order to avoid shorts or large leakage between the CRL and the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the PEDOT:PSS/PEI CRL used in those tandem cells required to be patterned (due to the high conductivity) in order to avoid shorts or large leakage between the CRL and the electrodes. 26,36,[38][39][40][41][42] For instance, Gupta et al 41 reported that their tandem solar cells exhibited electrical shorts between two PEDOT:PSS layers because of its lateral conductivity. Similar challenges have also been reported in recent papers.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have demonstrated polyethylenimine (PEI) is able to substantially reduce the work function of conductors such as metals, metal oxides, conducting polymers and graphene. 6 Later on it has been widely used to produce low-work function electrodes for semiconducting optoelectronics devices, such as organic (or perovsikte) solar cells, [7][8][9][10][11][12][13][14] organic (or inorganic) light emitting diodes, [15][16][17][18][19][20] organic photodetectors, [21][22] and organic (or inorganic) field effect transistors. [23][24][25][26][27] Generally, 2-methoxyethanol (MEA) has been used as the solvent to process the PEI and the modification layer is typically prepared by spin coating method.…”
Section: Introductionmentioning
confidence: 99%